Strong QCD from Hadron Structure Experiments - Brodsky, S.; Burkert, V. D.; Carman, D. S.; Chen, J. P.; Cui, Z.-F.; Döring, M.; Dosch, Hans Günter; Draayer, J.; Elouadrhiri, L.; Glazier, D. I.; Hiller Blin, A. N.; Horn, T.; et al. (International journal of modern physics. E, Nuclear physics, 2020)
The topical workshop Strong QCD from Hadron Structure Experiments took place at Jefferson Lab from November 6-9, 2019. Impressive progress in relating hadron structure observables to the strong QCD mechanisms has been achieved from the ab initio QCD description of hadron structure in a diverse array of methods in order to expose emergent phenomena via quasi-particle formation. The wealth of experimental data and the advances in hadron structure theory make it possible to gain insight into strong interaction dynamics in the regime of large quark-gluon coupling (the strong QCD regime), which will address the most challenging problems of the Standard Model on the nature of the dominant part of hadron mass, quark-gluon confinement, and the emergence of the ground and excited state hadrons, as well as atomic nuclei, from QCD. This workshop aimed to develop plans and to facilitate the future synergistic efforts between experimentalists, phenomenologists, and theorists working on studies of hadron spectroscopy and structure with the goal to connect the properties of hadrons and atomic nuclei available from data to the strong QCD dynamics underlying their emergence from QCD. These results pave the way for a future breakthrough extension in the studies of QCD with an Electron-Ion Collider in the U.S.
Gesehen am 08.02.2021